Integrating Mobile Display Energy Saving into Cloud-Based Video Streaming via Rate-Distortion-Display Energy Profiling - Liu, Qian; Yan, Zhisheng; Chen, Chang Wen (IEEE transactions on cloud computing, 2020)
Mobile displays have been recognized as the major contributors to the energy consumption of contemporary mobile video services. Existing display energy reduction (DER) algorithms focus on local video/image processing by utilizing the computation resources on the mobile devices. As such, a per-device DER strategy is highly inefficient from the systematic perspective since the same computation is repeated among millions of individual mobile devices. In this new era of cloud-based video streaming, a natural question to ask is can ubiquitous cloud resources be exploited to overcome these drawbacks. It is based on this motivation that we design a paradigm-shifting strategy to integrate the display energy saving engine into cloud-based video streaming in order to simultaneously benefit massive mobile devices with a one-time video processing in the cloud. By taking full advantage of the computational and storage resources in the cloud, a family of Rate-Distortion-Display Energy (R-D-DE) profiles can be created for a given video source and for different types of mobile devices. The preliminary experimental results with OLED displays prove that we can achieve the desired DER performance through jointly managing the display energy and user experience by implementing the proposed R-D-DE integrated video encoding engine in the cloud.